1993
DOI: 10.1121/1.406951
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sea ice cover on acoustic ray travel times, with applications to the Greenland Sea tomography experiment

Abstract: The travel-time effects of a sea ice cover on an acoustic pulse are estimated using generalized ray theory. This expands upon the previous work done by Jin and Wadhams [Prog. Oceanogr. 22, 249–275 (1989)] by including the effects of frequency dispersion and different sets of ice parameters. Travel-time changes due to single reflections are approximated by plane wave reflection theory, and compared to the generalized ray theory results. Statistical effects for multiple reflections, such as the ice thickness pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1994
1994
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…(ii) The use of acoustic techniques. It has been shown that travel time changes for an acoustic path are reduced by the presence of an ice cover, in most cases by an amount approximately proportional to the ice thickness (Guoliang and Wadhams 1989;Jin et al 1993). In long-range acoustic propagation experiments this can be used to give a single mean value for ice thickness along a path.…”
Section: Future Measurement Needsmentioning
confidence: 98%
“…(ii) The use of acoustic techniques. It has been shown that travel time changes for an acoustic path are reduced by the presence of an ice cover, in most cases by an amount approximately proportional to the ice thickness (Guoliang and Wadhams 1989;Jin et al 1993). In long-range acoustic propagation experiments this can be used to give a single mean value for ice thickness along a path.…”
Section: Future Measurement Needsmentioning
confidence: 98%
“…Nominal accuracy for the latter system is no better than AE0.5m in thickness. 13 Other, more exotic, thickness estimation methods also have been proposed based upon horizontal acoustic ray travel times 14,15 and from anomalous peaks in the flexural wave spectrum of floating ice covers. 16 In both cases, simplifying assumptions about the character of the ice covers appear to be difficult to justify.…”
Section: Above Surface Approachesmentioning
confidence: 99%
“…Acoustic experimental researches in the Arctic region can be traced back to the last century [3]. The ice area, climate, and earthquakes were monitored through the experimental data of underwater acoustic propagation [4,5].…”
Section: Introductionmentioning
confidence: 99%